Dietary fibers and associated phytochemicals in cereals. Issue 7 (13th January 2017) - Bach Knudsen, Knud Erik; Nørskov, Natalja P.; Bolvig, Anne Katrine; Hedemann, Mette Skou; Lærke, Helle Nygaard
Abstract : The underlying physiological mechanisms behind the protective health effects of whole‐grain cereals are unclear, but are most likely assigned to a concerted action of dietary fiber and a wide variety of phenolic phytochemicals. Only a small fraction of the phenolics is absorbed in the small but the availability can be increased by bioprocessing. Abstract : Epidemiological studies have linked whole‐grain (WG) cereal consumption to a reduced risk of developing several chronic diseases—coronary heart disease, arteriosclerosis, type‐2 diabetes, and some form of cancers. The underlying physiological mechanisms behind the protective effects of WG are unclear, but can most likely be assigned to a concerted action of dietary fiber (DF) and a wide variety of phytochemicals. Physiologically, it is important that soluble nonstarch polysaccharides contribute to higher viscosity in the small intestine as this may influence rate and extent of digestion and absorption. Associated with the DF matrix of cereals is an array of nonnutritive constituents predominantly concentrated in the bran fraction. Among them, the phenolic phytochemicals, benzoic acid and cinnamic derivatives and lignans, are of importance in a nutritional‐health perspective. Only a small fraction of the phenolics is absorbed in the small intestine, but the availability can be increased by bioprocessing. The major part, however, is passed to the large intestine where the microbiota, which degrade and metabolize DF to SCFAs and gases, also convert the phenolic compounds into a range of other metabolites that are absorbed into the body and with the capability of influencing the metabolism at the cellular level.